Preventive Effect of Lactobacillus acidophilus XY27 on DSS-Induced Ulcerative Colitis in Mice - Hu T; Wang H; Xiang C; Mu J; Zhao X (Dove Medical Press, 2020)
Tiantian Hu,1– 3,* Hongxia Wang,4,* Chengzheng Xiang,1– 3 Jianfei Mu,1– 3 Xin Zhao1– 3 1Chongqing Collaborative Innovation Center for Functional Food, Chongqing University of Education, Chongqing, People’s Republic of China; 2Chongqing Engineering Research Center of Functional Food, Chongqing University of Education, Chongqing, People’s Republic of China; 3Chongqing Engineering Laboratory for Research and Development of Functional Food, Chongqing University of Education, Chongqing, People’s Republic of China; 4Department of Paediatrics, Haikou Affiliated Hospital of Central South University Xiangya School of Medicine (Haikou People’s Hospital), Haikou, Hainan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xin Zhao Tel +86-23-6265-3650Email zhaoxin@cque.edu.cnIntroduction: Lactobacillus acidophilus is widely used as probiotic supplement in functional foods due to its beneficial regulatory effects on host, such as immune regulation, anti-inflammatory, and antioxidant activities.Aim: This study aimed to determine the preventive effect of Lactobacillus acidophilus XY27 (L. acidophilus XY27) on colitis induced by dextran sodium.Methods: The mice were randomly divided into five groups. Except for the control group, the other four groups were induced for ulcerative colitis (UC) with dextran sodium sulfate (DSS), and three groups in DSS-groups were treated with L. acidophilus XY27, L. bulgaricus, and salicylazosulfapyridine. The weight change, DAI score, colon length, and length to weight ratio were tested. The oxidation index and the levels of inflammatory cytokines in the serum were measured. Subsequently, the gene expression levels of inflammatory factors in the colon tissue were determined by the Real-Time quantitative polymerase chain reaction (qRT-PCR) method.Results: The results showed that the mice in the L. acidophilus XY27 group performed better in terms of weight, DAI score, colon length, and length to weight ratio or colonic pathological sections compared with the DSS-induced group. Further, the levels of tumor necrosis factor α (TNF-α), Interleukin-6 (IL-6), Interleukin-12 (IL-12) and Interleukin-1β (IL-1β), malondialdehyde (MDA) content, and myeloperoxidase activity in the serum of UC mice treated with L. acidophilus XY27 significantly decreased, while the levels of Interferon-γ (IFN-γ), Interleukin-10 (IL-10), Catalase (CAT), and total superoxide dismutase (SOD) significantly increased. The gene expression levels of Ets-like transcription factor-1 (EIK-1), IL-12, IL-1β, Cyclooxygenase 2 (COX-2), TNF-α, Escherichia coli, Lipopolysaccharide (LPS), and p100 in the colon significantly decreased while those of tight junction protein 1 (ZO-1), nuclear factor kappa B (NF-kB), p53, and NF-kappa-B inhibitor alpha (IκB-α) increased in the L. acidophilus XY27 group.Conclusion: The results of the experiment suggested that L. acidophilus XY27 prevented colitis and alleviated symptoms in mice with DSS-induced UC, and also repaired the intestinal barrier function.Keywords: dextran sodium sulfate, Lactobacillus acidophilus XY27, Lactobacillus bulgaricus, ulcerative colitis